Low-power internet of underwater things: vision and key technologies - Yang LIU; Cuican LI; Mugen PENG (物联网学报)
With the explosion of underwater sensing devices and the pursuit of energy conservation, the concept of low-power internet of underwater things has been put forward.Inspired by RF-based backscatter networks, the low-power internet of underwater things architecture uses underwater acoustic backscatter technology to realize the low-power and low-cost communication of underwater sensor nodes, which has a wide application prospect in underwater fields such as the long-term underwater detection.Firstly, the principle and architecture of low-power internet of underwater things was introduced.Then, the key technologies faced by the architecture were proposed and analyzed, such as perception, communication, networking, resource allocation, security and so on.Finally, the future research directions of low-power internet of underwater things were discussed.